Status of Infant and Young Child Feeding Practice and Its Association on Anthropometry in 6-24 Months Children in a Tertiary Care Hospital (Sir Salimullah Medical College Journal, 2026)
Background: In developing countries, around 32% of under-five children are stunted, and 10% are wasted. Sub-optimal breastfeeding and inappropriate complementary feeding practices are important causes of malnutrition. The aim of the study. The aim of study was to observe the status of infant and young child feeding (IYCF) practices and its impact on anthropometry among the patients attending in SSMCMH, Dhaka. Methods: This observational study was conducted at Sir Salimullah Medical College and Mitford Hospital, Dhaka, over a period of 6 months from July 2021 to December 2021 after approval of protocol. A written structured questionnaire was applied for data collection. The collected data was analyzed and presented as tabulated form. Results: Among the children, 45% infants were found initiated breastfeeding within one hour, 59.3% infants maintained exclusive breastfeeding upto six completed months and 78% continued breastfeeding upto one year of age. The rate of the timely starting of complementary feeding was 51.3%. Among the children, 15.2% were severely underweight and 26.8% were moderately underweight; 9.3% were severely stunted, and 20% were moderately stunted; 6.5% were severely wasted and 15.5% were moderately wasted. Conclusion: It is demonstrated in this study that there is a significant positive effect of IYCF on nutritional status measured by anthropometry. But there needs more emphasis to improve the current IYCF practice to meet the goal of SDG. Mothers should be encouraged for initiation of breastfeeding within one-hour, exclusive breast feeding for 6 months and use nutritious foods during complementary feeding.Sir Salimullah Med Coll J 2025; 33: 45-52